High-temperature-resistant low-shrinkage aerogel thermal insulation coating and preparation method thereof

CN122898167APending Publication Date: 2026-10-13ZHONGZENG TECHNOLOGY (SUZHOU) CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611154908.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-07-31
Publication Date
2026-10-13

AI Technical Summary

Technical Problem

[0003]本发明的目的在于提供一种耐高温低收缩气凝胶隔热保温涂料及其制备方法,以解决上述背景技术中提出的技术问题

Benefits of technology

本发明通过氧化铝溶胶与氧化锆溶胶复配的无机粘结剂体系、多尺度纤维分级增强结构以及部分疏水改性纤维的协同应力调控机制,使涂层干燥收缩率稳定控制在0.2%以下,并实现了单次刮涂厚度3mm以上干燥不开裂、不脱落的厚涂施工性能,显著优于现有气凝胶隔热涂料普遍存在的0.5%以上收缩率及难以厚涂的技术缺陷;同时,优选SiOC气凝胶的高温稳定性与氧化锆在高温下相变增韧产生的体积膨胀效应相互协同,有效抵消了涂层在高温服役过程中的烧结收缩,使800℃热处理后线收缩率控制在0.5%以下,远优于现有技术1%以上的高温收缩水平,且SiOC气凝胶表面形成的碳氧化硅保护层延缓了骨架氧化烧结,克服了传统SiO2气凝胶在600℃以上孔隙坍塌的技术瓶颈;此外,通过气凝胶纳米多孔结构抑制气体对流传热与固体热传导、多尺度纤维阻断热流直线传递、红外抑制填料散射反射高温红外辐射的三重隔热机制协同作用,使涂层导热系数低至0.035W/(m·K),兼顾了常温与高温下的高效隔热;本发明为全水性无机体系,无VOCs排放,环境友好,可灵活采用刮涂、喷涂、刷涂等多种施工方式,适用于工业炉窑、高温管道、石油化工设备、航空航天热防护及建筑保温等领域,兼具高性能、易施工与绿色环保的显著优势。

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The application discloses a kind of high-temperature-resistant low-shrinkage aerogel heat-insulating coating and preparation method thereof, it is related to inorganic heat-insulating coating technical field, including the following weight parts of raw material component: inorganic binder system 20~50 parts;Hydrophobic modified aerogel particle 5~25 parts;First inorganic fiber 3~15 parts;Second inorganic fiber 1~8 parts;Infrared suppression filler 2~10 parts;Dispersing agent 0.5~3 parts;Thickening agent 0.5~4 parts;Defoaming agent 0.1~1 parts;Water 15~40 parts.The application is by the inorganic binder system of alumina sol and zirconia sol complex, multi-scale fiber hierarchical reinforced structure and the synergistic stress regulation mechanism of part hydrophobic modified fiber, makes coating dry shrinkage rate stable control at 0.2% below, and realizes single time to be scraped with the construction performance of 3mm above dryness not cracking, not falling off thick coating, significantly superior to the technical defects of 0.5% or more shrinkage and difficult thick coating generally existing in prior art aerogel heat-insulating coating.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of inorganic thermal insulation coating technology, specifically to a high-temperature resistant, low-shrinkage aerogel thermal insulation coating and its preparation method. Background Technology

[0002] Aerogel, a novel functional material with a nanoporous network structure, typically boasts a porosity exceeding 90% and a thermal conductivity as low as 0.018 W / (m·K), making it one of the best-performing solid materials in terms of overall thermal insulation performance. Thermal insulation coatings prepared using aerogel as a functional filler combine excellent thermal insulation properties, ease of application, and good adaptability to irregular surfaces, making them an important development direction in the field of thermal insulation and possessing broad application prospects in industrial energy conservation and thermal protection. Currently, aerogel thermal insulation coatings mainly face the following technical bottlenecks: First, existing inorganic coatings use water glass, phosphates, etc. as binders. Although they have good temperature resistance, the coating experiences stress concentration during drying and high-temperature service, making it prone to shrinkage cracking. Furthermore, the thickness of a single application is usually limited to less than 1 mm, severely restricting construction efficiency. Second, silica aerogels are prone to sintering and pore collapse in high-temperature environments (>600℃), leading to a sharp decline in thermal insulation performance and further exacerbating volume shrinkage. Third, achieving good thermal insulation requires a high aerogel addition amount, but excessive addition weakens the coating strength and toughness, exacerbating drying shrinkage and resulting in a shrinkage rate generally as high as 0.5%~1.2%, or even higher. The micro-cracks and gaps generated by shrinkage form thermal bridge channels, significantly reducing the thermal insulation effect. Therefore, how to significantly reduce the drying and high-temperature shrinkage rates of the coating while ensuring excellent high-temperature resistance and low thermal conductivity, and achieving a single application of thick coatings without cracking or peeling, is a core technical challenge that urgently needs to be solved in this field. Summary of the Invention

[0003] The purpose of this invention is to provide a high-temperature resistant, low-shrinkage aerogel thermal insulation coating and its preparation method, so as to solve the technical problems mentioned in the background art.

[0004] To achieve the above objectives, the present invention provides the following technical solution: a high-temperature resistant, low-shrinkage aerogel thermal insulation coating, comprising the following raw material components in parts by weight: 20-50 parts of inorganic binder system; 5-25 parts of hydrophobic modified aerogel particles; 3-15 parts of first inorganic fiber; The following components are described: 1-8 parts of second inorganic fiber; 2-10 parts of infrared suppressing filler; 0.5-3 parts of dispersant; 0.5-4 parts of thickener; 0.1-1 parts of defoamer; and 15-40 parts of water. The inorganic binder system comprises alumina sol and zirconium oxide sol, with a mass ratio of (2-5):1. The hydrophobically modified aerogel particles are hydrophobically modified SiOC aerogel particles or hydrophobically modified SiO2 aerogel particles, with a particle size of 1-50 μm and a specific surface area ≥500 m². 2 / g, contact angle ≥130°; the first inorganic fiber is a short chopped fiber with a length of 2~6mm, selected from at least one of ceramic fiber, glass fiber, and aluminosilicate fiber, wherein a portion of the fiber is hydrophobically modified, and the hydrophobically modified fiber accounts for 20%~60% of the total amount of the first inorganic fiber; the second inorganic fiber is a microfiber with a length of 0.1~1mm, selected from at least one of wollastonite fiber, sepiolite fiber, and brucite fiber; the infrared suppressing filler is selected from at least one of nano TiO2, nano SiC, nano ZrO2, and potassium titanate whiskers.

[0005] Preferably, the solid content of the alumina sol is 15% to 30%, and the solid content of the zirconium oxide sol is 10% to 25%.

[0006] Preferably, the hydrophobically modified aerogel particles are hydrophobically modified SiOC aerogel particles with a thermal conductivity ≤0.025 W / (m·K) and a pore size distribution of 2~50 nm.

[0007] Preferably, the infrared suppressing filler is a mixture of nano-TiO2 and nano-SiC, with a mass ratio of nano-TiO2 to nano-SiC of (1~3):1.

[0008] Preferably, the dispersant is at least one of sodium polyacrylate, polyethylene glycol, and sodium hexametaphosphate; and the thickener is at least one of hydroxyethyl cellulose, hydroxypropyl methylcellulose, and bentonite.

[0009] Preferably, it includes the following steps: Step 1: Fiber pretreatment: Immerse the first inorganic fiber in a hydrophobic modifier solution for 30-120 minutes, then remove and dry at 80-120℃ to obtain hydrophobic modified fiber; subject the second inorganic fiber to mechanical dispersion treatment to fully deagglomerate the fiber. Step 2, Slurry preparation: Add water, dispersant, thickener and defoamer to a mixing container and stir at 300~600 r / min for 10~30 min to fully dissolve and disperse the additives; Step 3, Fiber dispersion: Add the first and second inorganic fibers treated in Step 1 to the mixture obtained in Step 2, and shear and disperse them at a high speed of 800~1500 r / min for 20~60 min to make the fibers uniformly dispersed in the system. Step 4: Adding aerogel: Reduce the rotation speed to 200~400 r / min, slowly add the hydrophobic modified aerogel particles to the system, and continue stirring for 15~40 min to make the aerogel particles evenly dispersed. Step 5: Adding binder and filler: Add the inorganic binder system and infrared suppressor filler to the system, and stir at a speed of 400~800 r / min for 20~50 min to obtain a uniform coating slurry; Step 6, Aging: Aging the coating slurry obtained in Step 5 at room temperature for 12~48 hours to obtain a high-temperature resistant, low-shrinkage aerogel thermal insulation coating.

[0010] Preferably, the hydrophobic modifier solution in step one is a silane coupling agent ethanol solution with a mass fraction of 1% to 5%, wherein the silane coupling agent is selected from at least one of KH-550, KH-570, and hexamethyldisilazane.

[0011] Preferably, the slow addition method described in step four is to add the aerogel particles in batches, with each batch containing 20% ​​to 30% of the total aerogel particles, and the interval between two adjacent batches being 3 to 8 minutes.

[0012] Compared with the prior art, the beneficial effects of the present invention are: This invention utilizes an inorganic binder system composed of alumina sol and zirconia sol, a multi-scale fiber-reinforced structure, and a synergistic stress regulation mechanism involving partially hydrophobically modified fibers to stably control the coating's drying shrinkage rate below 0.2%. It also achieves thick-coating performance with a single application thickness exceeding 3mm, without cracking or peeling during drying. This significantly surpasses the technical shortcomings of existing aerogel thermal insulation coatings, which generally exhibit shrinkage rates exceeding 0.5% and difficulty in achieving thick coatings. Furthermore, the optimal combination of the high-temperature stability of SiOC aerogel and the volume expansion effect generated by the phase transformation toughening of zirconia at high temperatures effectively offsets the sintering shrinkage of the coating during high-temperature service. This results in a linear shrinkage rate below 0.5% after heat treatment at 800℃, far exceeding the high-temperature shrinkage level of over 1% in existing technologies. The carbon oxide protective layer formed on the adhesive surface delays the sintering of the skeleton oxidation, overcoming the technical bottleneck of pore collapse in traditional SiO2 aerogels above 600℃. In addition, through the synergistic effect of the triple thermal insulation mechanism of the aerogel nanoporous structure inhibiting gas convection heat transfer and solid heat conduction, multi-scale fibers blocking the linear heat transfer, and infrared suppression of filler scattering and reflection of high-temperature infrared radiation, the thermal conductivity of the coating is as low as 0.035W / (m·K), achieving high-efficiency thermal insulation at both room temperature and high temperature. This invention is a fully water-based inorganic system with no VOC emissions, making it environmentally friendly. It can be flexibly applied using various construction methods such as scraping, spraying, and brushing, and is suitable for industrial furnaces, high-temperature pipelines, petrochemical equipment, aerospace thermal protection, and building insulation, with significant advantages of high performance, easy construction, and green environmental protection. Detailed Implementation

[0013] The technical solutions in the embodiments of the present invention will be clearly and completely described below. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.

[0014] This embodiment provides a high-temperature resistant, low-shrinkage aerogel thermal insulation coating, comprising the following raw material components in parts by weight: 35 parts of an inorganic binder system (alumina sol to zirconia sol in a mass ratio of 3:1, alumina sol solid content of 22%, zirconia sol solid content of 18%); 15 parts of hydrophobically modified SiOC aerogel particles (particle size of 10~30μm, specific surface area of ​​580 m²). 2 / g, contact angle 135°, thermal conductivity 0.022 W / (m·K)); 8 parts of first inorganic fiber (ceramic fiber, length 3~5mm, of which 40% is hydrophobically modified by KH-550); 4 parts of second inorganic fiber (wollastonite fiber, length 0.2~0.8mm); 5 parts of infrared suppressing filler (nano TiO2 and nano SiC mixed at a mass ratio of 2:1); 1.5 parts of dispersant (sodium polyacrylate); 2 parts of thickener (hydroxyethyl cellulose); 0.5 parts of defoamer; 29 parts of water.

[0015] The preparation method is as follows: Step 1: Fiber pretreatment: The ceramic fibers are immersed in a 3% KH-550 ethanol solution for 60 minutes, then dried at 100℃ to obtain hydrophobic modified ceramic fibers; the wollastonite fibers are mechanically dispersed to fully deagglomerate the fibers. Step 2, Slurry preparation: Add water, sodium polyacrylate, hydroxyethyl cellulose and defoamer to a mixing container and stir at 400 r / min for 20 min to fully dissolve and disperse the additives; Step 3, Fiber dispersion: Add the ceramic fibers and wollastonite fibers treated in Step 1 to the mixture obtained in Step 2, and shear and disperse them at a high speed of 1200 r / min for 40 min to make the fibers uniformly dispersed in the system. Step 4: Aerogel addition: Reduce the rotation speed to 300 r / min and add hydrophobically modified SiOC aerogel particles to the system in 5 batches. Each batch contains 3 parts (i.e., 20% of the total aerogel particles). The interval between two adjacent batches is 5 min. After all the particles are added, continue stirring for 30 min to ensure that the aerogel particles are evenly dispersed and that their porous structure is not damaged. Step 5: Adding binders and fillers: Add alumina sol, zirconium oxide sol, and a mixture of nano-TiO2 and nano-SiC to the system, and stir at 600 r / min for 35 min to obtain a uniform coating slurry; Step 6, Aging: Aging the coating slurry obtained in Step 5 at room temperature for 24 hours yields a high-temperature resistant, low-shrinkage aerogel thermal insulation coating.

[0016] The coating obtained in this embodiment was applied to the surface of a stainless steel substrate by scraping, with a single scraping thickness of 3.5 mm. After drying at room temperature for 48 hours, the coating surface was smooth, without cracks or peeling.

[0017] This embodiment provides a high-temperature resistant, low-shrinkage aerogel thermal insulation coating, comprising the following raw material components in parts by weight: 40 parts of an inorganic binder system (alumina sol to zirconia sol in a mass ratio of 4:1, alumina sol solid content of 25%, zirconia sol solid content of 20%); 20 parts of hydrophobically modified SiO2 aerogel particles (particle size of 5~40μm, specific surface area of ​​620 m²). 2 / g, contact angle 132°); 10 parts of first inorganic fiber (aluminosilicate fiber, length 2~4mm, of which 50% is treated with KH-570 hydrophobic modification); 3 parts of second inorganic fiber (sepiolite fiber, length 0.1~0.5mm); 6 parts of infrared suppressing filler (potassium titanate whiskers, diameter 0.5~1μm, aspect ratio >20); 2 parts of dispersant (sodium hexametaphosphate); 3 parts of thickener (bentonite); 0.8 parts of defoamer; water balance (to 100 parts).

[0018] The preparation method is the same as in Example 1, except that: in step one, the aluminosilicate fibers are immersed in a 4% KH-570 ethanol solution for 90 min and then dried at 110℃; in step two, the stirring speed is 500 r / min and the stirring time is 15 min; in step three, the high-speed shearing speed is 1000 r / min and the dispersion time is 50 min; in step four, aerogel particles (25% per batch) are added in four batches with an interval of 6 min, a stirring speed of 250 r / min and a stirring time of 25 min; in step five, the stirring speed is 500 r / min and the stirring time is 40 min; and in step six, the aging time is 36 h.

[0019] The coating obtained in this embodiment was applied to the surface of a stainless steel substrate by scraping. The thickness of a single scraping was 3.2 mm. After drying at room temperature for 48 hours, the coating surface was smooth, without cracks or peeling.

[0020] This embodiment provides a high-temperature resistant, low-shrinkage aerogel thermal insulation coating, comprising the following raw material components in parts by weight: 28 parts of an inorganic binder system (alumina sol to zirconia sol mass ratio of 2.5:1, alumina sol solid content of 20%, zirconia sol solid content of 15%); 12 parts of hydrophobically modified SiOC aerogel particles (particle size of 20~50μm, specific surface area of ​​540 m²). 2 / g, contact angle 138°); 14 parts of the first inorganic fiber (glass fiber, length 4~6mm, of which 55% is hydrophobically modified with hexamethyldisilazane); 2 parts of the second inorganic fiber (brucite fiber, length 0.3~0.7mm); 8 parts of infrared suppressing filler (nano ZrO2, average particle size 50nm); 1 part of dispersant (polyethylene glycol); 1.5 parts of thickener (hydroxypropyl methylcellulose); 0.3 parts of defoamer; 33.2 parts of water.

[0021] The preparation method is as follows: Step 1: Fiber pretreatment: The glass fiber is immersed in a 2% (w / w) hexamethyldisilazane ethanol solution for 120 min, then dried at 80℃ to obtain hydrophobic modified glass fiber; the brucite fiber is mechanically dispersed to fully deagglomerate the fiber. Step 2, Slurry preparation: Add water, polyethylene glycol, hydroxypropyl methylcellulose and defoamer to a mixing container and stir at 350 r / min for 30 min to fully dissolve and disperse the additives; Step 3, Fiber dispersion: Add the glass fiber and magnesia fiber treated in Step 1 to the mixture obtained in Step 2, and shear and disperse them at a high speed of 1400 r / min for 30 min to make the fibers uniformly dispersed in the system. Step 4: Aerogel addition: Reduce the rotation speed to 350 r / min and add hydrophobically modified SiOC aerogel particles to the system in 4 batches. Each batch contains 3 parts (i.e., 25% of the total aerogel particles). The interval between two adjacent batches is 4 min. After all the particles are added, continue stirring for 20 min. Step 5: Adding binders and fillers: Add alumina sol, zirconium oxide sol and nano ZrO2 to the system, and stir at 700 r / min for 25 min to obtain a uniform coating slurry; Step 6, Aging: Aging the coating slurry obtained in Step 5 at room temperature for 18 hours to obtain the final product.

[0022] The coating obtained in this embodiment was applied to the surface of a carbon steel substrate by spraying. The thickness of the wet film after a single spray was about 3 mm, and the thickness of the coating after drying was about 2.8 mm. There were no cracks or peeling on the surface.

[0023] This embodiment provides a high-temperature resistant, low-shrinkage aerogel thermal insulation coating, comprising the following raw material components in parts by weight: 45 parts of an inorganic binder system (alumina sol to zirconia sol mass ratio of 4.5:1, alumina sol solid content of 28%, zirconia sol solid content of 22%); 22 parts of hydrophobically modified SiO2 aerogel particles (particle size of 1~20μm, specific surface area of ​​650 m²). 2 / g, contact angle 140°); 6 parts of the first inorganic fiber (ceramic fiber and aluminosilicate fiber mixed in a 1:1 mass ratio, length 3~5mm, of which 30% is treated with KH-550 hydrophobic modification); 7 parts of the second inorganic fiber (wollastonite fiber and sepiolite fiber mixed in a 1:1 mass ratio, length 0.1~0.6mm); 4 parts of infrared suppressing filler (nano TiO2 and nano SiC mixed in a 3:1 mass ratio); 2.5 parts of dispersant (sodium polyacrylate and sodium hexametaphosphate mixed in a 1:1 mass ratio); 3.5 parts of thickener (hydroxyethyl cellulose and bentonite mixed in a 2:1 mass ratio); 0.6 parts of defoamer; water balance (to 100 parts).

[0024] The preparation method is as follows: Step 1: Fiber pretreatment: The mixture of ceramic fiber and aluminosilicate fiber is immersed in a 4.5% KH-550 ethanol solution for 45 minutes, and then dried at 115℃ to obtain hydrophobic modified mixed fiber; The mixture of wollastonite fiber and sepiolite fiber is mechanically dispersed to fully deagglomerate the fibers. Step 2, Slurry preparation: Add water, sodium polyacrylate, sodium hexametaphosphate, hydroxyethyl cellulose, bentonite and defoamer to a mixing container and stir at 550 r / min for 12 min to fully dissolve and disperse the additives. Step 3, Fiber dispersion: Add all the fibers treated in Step 1 to the mixture obtained in Step 2, and shear and disperse them at a high speed of 900 r / min for 55 min to ensure that the fibers are uniformly dispersed in the system. Step 4: Adding aerogel: Reduce the rotation speed to 220 r / min and add hydrophobically modified SiO2 aerogel particles to the system in 5 batches. Each batch contains 4.4 parts (i.e. 20% of the total aerogel particles). The interval between two adjacent batches is 7 min. After all the particles are added, continue stirring for 35 min. Step 5: Adding binders and fillers: Add alumina sol, zirconium oxide sol, and a mixture of nano-TiO2 and nano-SiC to the system, and stir at 750 r / min for 45 min to obtain a uniform coating slurry; Step 6, Aging: Aging the coating slurry obtained in Step 5 at room temperature for 40 hours to obtain the final product.

[0025] The coating obtained in this embodiment was applied to the surface of the refractory brick substrate by scraping. The thickness of a single scraping was 3.8 mm. After drying at room temperature for 72 hours, the coating surface was smooth and dense, without cracks or peeling.

[0026] Working principle: Volume shrinkage of coatings during drying, curing, and high-temperature service is a major cause of cracking and insulation failure. This invention effectively suppresses shrinkage stress by constructing a composite network structure of "inorganic binder skeleton + multi-scale fiber reinforcement." Specifically, alumina sol forms a continuous Al-O-Al three-dimensional gel network during drying, providing the coating's basic structural strength and adhesion; zirconia sol uniformly fills the gaps in this network, partially reinforcing Zr at high temperatures. 4+ The inorganic framework is further strengthened by the formation of a solid solution within the Al2O3 lattice. Building upon this, a first inorganic fiber (chopped fiber) with a length of 2–6 mm serves as a macroscopic reinforcing phase, bridging microcracks and weak interfaces within the coating. The fiber's bridging and pull-out effects dissipate energy for crack propagation. A second inorganic fiber (microfiber) with a length of 0.1–1 mm fills the microscopic region between the chopped fiber and the binder matrix, forming denser fiber anchor points and reducing the reinforcement blind spots left by single-scale fibers. The synergistic effect of these two fiber scales allows stress to be transferred to the fiber network through the fiber-matrix interface during drying shrinkage, with the fibers bearing most of the tensile stress, thus significantly reducing stress concentration within the matrix. More importantly, 20%–60% of the first inorganic fiber undergoes hydrophobic modification, changing its surface from hydrophilic to hydrophobic. This reduces the interfacial bonding strength between the fiber and the inorganic binder to an appropriate level—if the bonding is too strong, the fiber will shrink synchronously with the matrix and lose its reinforcing effect; if the bonding is too weak, the fiber cannot effectively transfer stress. The appropriate hydrophobic modification ratio enables the fiber to generate controllable micro-slippage when the matrix shrinks, releasing some of the shrinkage stress, while still maintaining sufficient anchoring force to play a bridging role. Ultimately, the drying shrinkage rate is controlled below 0.2%, and a single coating thickness of more than 3 mm is achieved without cracking.

[0027] The thermal insulation performance of thermal insulation coatings depends on their comprehensive ability to suppress three heat transfer modes (solid-to-solid heat conduction, gas convection heat transfer, and infrared radiation heat transfer). This invention achieves high-efficiency thermal insulation through a triple approach of "aerogel porous structure + fiber barrier + infrared suppression filler". First, the hydrophobically modified aerogel particles have extremely high nanoporosity (porosity >90%, pore size 2~50nm), and their pore size is smaller than the mean free path of gas molecules in the air (approximately 70nm), preventing gas molecules within the pores from effectively colliding and transferring heat, thus greatly suppressing gas convection heat transfer. At the same time, the nanoskeleton of the aerogel is a highly branched chain structure, which greatly extends the solid-to-solid heat conduction path and effectively reduces the solid-to-solid heat transfer efficiency. Second, the multi-scale inorganic fibers uniformly dispersed in the coating not only play a reinforcing role, but their own low thermal conductivity and the microporous interface formed between the fibers and the matrix further block the straight-line heat flow within the coating, forcing heat to be conducted along a tortuous path. Furthermore, when the coating operates at high temperatures (e.g., above 800°C), infrared radiation heat transfer gradually becomes the dominant heat transfer mode. The infrared suppressing fillers added in this invention, such as nano-TiO2, nano-SiC, nano-ZrO2, or potassium titanate whiskers, have high refractive index and high infrared reflectivity, which can effectively scatter and reflect infrared radiation waves at high temperatures, reflecting radiant heat back towards the heat source. The three heat insulation mechanisms complement each other at the macroscopic to nanoscale, enabling the thermal conductivity of the coating to be as low as below 0.035 W / (m·K).

[0028] Traditional SiO2 aerogels undergo surface hydroxyl condensation and particle sintering at high temperatures (>600℃), leading to the collapse of the nanoporous structure and a sharp decrease in specific surface area, resulting in deteriorated thermal insulation performance and increased volume shrinkage. This invention preferentially uses SiOC aerogel as a functional filler. Its framework is composed of Si-O-C covalent bonds, with carbon elements embedded in the silicon-oxygen network in the forms of Si-CH3 and Si-C-Si, forming an amorphous network with higher bond energy and a more stable structure. In a high-temperature oxidizing environment, the silica protective layer formed on the surface of SiOC aerogel effectively inhibits oxygen diffusion into the interior, delaying the oxidation and sintering of the framework structure, allowing it to maintain a relatively intact nanoporous structure even above 800℃. Simultaneously, the zirconium oxide sol in the inorganic binder system undergoes a martensitic phase transformation from a tetragonal phase to a monoclinic phase at high temperatures (approximately 600~800℃), accompanied by a volume expansion effect of approximately 3%~5%. This invention utilizes a phase transformation toughening mechanism—the volume expansion of ZrO2 at high temperatures partially offsets the high-temperature sintering shrinkage of the aerogel and binder matrix, significantly reducing the overall linear shrinkage of the coating during high-temperature service. The alumina sol transforms into γ-Al2O3 at high temperatures and gradually transitions to α-Al2O3, forming a dense and stable ceramic bonding phase that firmly binds the aerogel particles, fibers, and infrared suppressor fillers together, ensuring the coating maintains structural integrity and dimensional stability under long-term high-temperature conditions.

[0029] It will be apparent to those skilled in the art that the present invention is not limited to the details of the exemplary embodiments described above, and that the invention can be implemented in other specific forms without departing from the spirit or essential characteristics of the invention. Therefore, the embodiments should be considered in all respects as exemplary and non-limiting, and the scope of the invention is defined by the appended claims rather than the foregoing description. Thus, it is intended that all variations falling within the meaning and scope of equivalents of the claims be included within the present invention.

Claims

1. A high-temperature resistant, low-shrinkage aerogel thermal insulation coating, characterized in that, The raw material components include the following parts by weight: 20-50 parts of inorganic binder system; 5-25 parts of hydrophobically modified aerogel particles; 3-15 parts of first inorganic fiber; 1-8 parts of second inorganic fiber; 2-10 parts of infrared suppressing filler; Dispersant 0.5-3 parts; thickener 0.5-4 parts; defoamer 0.1-1 parts; water 15-40 parts; the inorganic binder system comprises alumina sol and zirconium oxide sol, with a mass ratio of alumina sol to zirconium oxide sol of (2-5):1; the hydrophobically modified aerogel particles are hydrophobically modified SiOC aerogel particles or hydrophobically modified SiO2 aerogel particles, with a particle size of 1-50 μm and a specific surface area ≥500 m². 2 / g, contact angle ≥130°; the first inorganic fiber is a short chopped fiber with a length of 2~6mm, selected from at least one of ceramic fiber, glass fiber, and aluminosilicate fiber, wherein a portion of the fiber is hydrophobically modified, and the hydrophobically modified fiber accounts for 20%~60% of the total amount of the first inorganic fiber; the second inorganic fiber is a microfiber with a length of 0.1~1mm, selected from at least one of wollastonite fiber, sepiolite fiber, and brucite fiber; the infrared suppressing filler is selected from at least one of nano TiO2, nano SiC, nano ZrO2, and potassium titanate whiskers.

2. The high-temperature resistant, low-shrinkage aerogel thermal insulation coating and its preparation method according to claim 1, characterized in that: The solid content of the alumina sol is 15% to 30%, and the solid content of the zirconium oxide sol is 10% to 25%.

3. The high-temperature resistant, low-shrinkage aerogel thermal insulation coating and its preparation method according to claim 1, characterized in that: The hydrophobically modified aerogel particles are hydrophobically modified SiOC aerogel particles with a thermal conductivity ≤0.025 W / (m·K) and a pore size distribution of 2~50 nm.

4. The high-temperature resistant, low-shrinkage aerogel thermal insulation coating and its preparation method according to claim 1, characterized in that: The infrared suppressing filler is a mixture of nano-TiO2 and nano-SiC, with a mass ratio of nano-TiO2 to nano-SiC of (1~3):

1.

5. The high-temperature resistant, low-shrinkage aerogel thermal insulation coating and its preparation method according to claim 1, characterized in that: The dispersant is at least one of sodium polyacrylate, polyethylene glycol, and sodium hexametaphosphate; the thickener is at least one of hydroxyethyl cellulose, hydroxypropyl methyl cellulose, and bentonite.

6. The method for preparing a high-temperature resistant, low-shrinkage aerogel thermal insulation coating according to any one of claims 1-5, characterized in that: Includes the following steps: Step 1: Fiber pretreatment: Immerse the first inorganic fiber in a hydrophobic modifier solution for 30-120 minutes, then remove and dry at 80-120℃ to obtain hydrophobic modified fiber; The second inorganic fiber is mechanically dispersed to fully deagglomerate the fibers; Step 2, Slurry preparation: Add water, dispersant, thickener and defoamer to a mixing container and stir at 300~600 r / min for 10~30 min to fully dissolve and disperse the additives; Step 3, Fiber dispersion: Add the first and second inorganic fibers treated in Step 1 to the mixture obtained in Step 2, and shear and disperse them at a high speed of 800~1500 r / min for 20~60 min to make the fibers uniformly dispersed in the system. Step 4: Adding aerogel: Reduce the rotation speed to 200~400 r / min, slowly add the hydrophobic modified aerogel particles to the system, and continue stirring for 15~40 min to make the aerogel particles evenly dispersed. Step 5: Adding binder and filler: Add the inorganic binder system and infrared suppressor filler to the system, and stir at a speed of 400~800 r / min for 20~50 min to obtain a uniform coating slurry; Step 6, Aging: Aging the coating slurry obtained in Step 5 at room temperature for 12~48 hours to obtain a high-temperature resistant, low-shrinkage aerogel thermal insulation coating.

7. The high-temperature resistant, low-shrinkage aerogel thermal insulation coating and its preparation method according to claim 6, characterized in that: The hydrophobic modifier solution mentioned in step one is a silane coupling agent ethanol solution with a mass fraction of 1% to 5%, wherein the silane coupling agent is selected from at least one of KH-550, KH-570, and hexamethyldisilazane.

8. The high-temperature resistant, low-shrinkage aerogel thermal insulation coating and its preparation method according to claim 6, characterized in that: The slow addition method described in step four is to add in batches, with each batch containing 20% ​​to 30% of the total amount of aerogel particles, and the interval between two adjacent batches being 3 to 8 minutes.